The determinants of growth performance of small services enterprises in Yemen - Alhammadi, Abdulnaser; Faridah Shahadan (Penerbit Universiti Kebangsaan Malaysia, 2014)
This study investigated the determinants of growth performance of the small service enterprises (SSEs) in Yemen. It examined how the management capabilities’ determinants (financial operations, firm marketing and firm management), business environment determinants (macroeconomic determinants and lack of capital) and firm resources (ease of doing business, personal traits and owner characteristics) influence the performance growth of small service enterprises. The data was collected through a survey administered to 170 samples in two cites: Sana’a and Taiz in Yemen. In using the method of the structural equation modelling (SEM) based on SPSS and AMOS programs, the results found that management capabilities determinants and business environment determinants affected the growth performance of small service enterprises in the country, but the firm resources determinants did not show statically significant impacts on these enterprises in Yemen.